2019
DOI: 10.1177/0971721819873179
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping the Business Incubator Model: The Case of the Value Chain Model of Innovation Works in China

Abstract: Since the late 1980s, the business incubator model in China has been evolving—from the early traditional model that focused mainly on providing basic services, such as office space and one-stop administrative services, to an emerging value chain model (value position, value creation, value transfer and value capture), which efficiently combines the profits of an incubator with the success of its incubating tenant ventures. This article analyses the case of ‘Innovation Works’, which is one of the pioneers of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
5
0
3
Order By: Relevance
“…Most of the research on entrepreneurial incubators currently selects entrepreneurial incubators dominated by the government or large companies [18,19] and analyzes the impact of different business operation models on the performance of incubating enterprises from the perspective of investment [20,21]. Few scholars have conducted in-depth research on this topic from the professional level of incubators.…”
Section: Related Workmentioning
confidence: 99%
“…Most of the research on entrepreneurial incubators currently selects entrepreneurial incubators dominated by the government or large companies [18,19] and analyzes the impact of different business operation models on the performance of incubating enterprises from the perspective of investment [20,21]. Few scholars have conducted in-depth research on this topic from the professional level of incubators.…”
Section: Related Workmentioning
confidence: 99%
“…Inkubator dapat memperkuat ekosistem kewirausahaan dengan mendukung startup lokal (VanWeele et al, 2018). Inkubator pertama kali muncul adalah Sillicon Valley San Fransisco (dimana mayoritas perusahaan bergerak di bidang computer), kemundian model inkubator berkembang sampai saat ini (Tang et al, 2019). Sillicon valey merupakan kerja sama triple helix antara universitas Standford Amerika, pemerintah dan dunia usaha (Firmansyah & Suman, 2021).…”
Section: Model Inkubasiunclassified
“…The university patent innovation value chain, UPIVC for short, refers to the process of knowledge innovation, application and commercialization that makes the patent value increase continuously and realizes the amplification of economic benefits. Since Hage and Hollingsworth proposed the concept of the innovation chain in 2000 [2], many scholars have been integrating it with practice [3]. Roper et al (2008) concluded that the innovation value chain was comprised of the recursive process of knowledge sourcing, transformation and exploitation [4].…”
Section: Conceptual Frameworkmentioning
confidence: 99%